Cultural Content and Foreign Language Public Speaking Anxiety: Contributing Factors and Culture-Based Coping Strategies in EFL Students - Himala Praptami Adys; Misnawaty Usman; Ernawati (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study investigates the relationship between cultural content integration and foreign language public speaking anxiety (FLPSA) among English as a Foreign Language (EFL) students. The research examines how incorporating Buginese cultural values (Sipakainga’, Sipakalebbi’, and Sipakatau’) affects anxiety levels and provides culture-based coping strategies for 56 Indonesian university students enrolled in Business English Communication program, Universitas Makassar. Using a mixed-methods approach, this study analyzed anxiety patterns, cultural identity impacts, and effectiveness of culturally-responsive pedagogical approaches. Results indicate that students who engaged with familiar cultural content demonstrated significantly lower anxiety levels and improved speaking performance compared to those exposed to purely Western-oriented materials. The findings suggest that integrating local cultural frameworks can serve as effective anxiety-reduction mechanisms while maintaining language learning objectives. This research contributes to understanding culturally-sensitive EFL pedagogy and provides practical implications for educators working with culturally homogeneous student populations.